PARQUE NACIONAL DOS CAMPOS GERAIS – PR: OPORTUNIDADES PARA COMUNIDADES DE ENTORNO - Baptista, Leandro (2013)
The tourism planning is a necessary tool for the activity development in line with the environmental, social, cultural and economic principles. For the other hand, the interest about conserving nature, can be understood to ensure the protection of examples of biodiversity and geodiversity, which it will be inherited by future generations, while at the present pace of environmental change caused by human activities is given in large scale and often impossible to be reversed. Therefore, this study has the Parque Nacional dos Campos Gerais (PNCG) as its object of study, located in the cities of Ponta Grossa, Castro and Carambeí, Parana centraleastern. The main objective seeks to perform an analysis of the future impacts generated by deploying PNCG for communities around this area, such as potential insertion of these with the Ecotourism activity. The specific objectives sought to make a diagnosis on the local communities perception regarding this Conservation Unity to assess the interest of these people to develop projects related to Ecotourism; suggest activities based on communitybased Ecotourism, which is characterized by the provision of services or products offered by the local community, and identify the potential tourism resources recognized by residents able to attract the interest of visitation in areas inside or around the PNCG. To achieve the objectives listed above, it was conducted semi-structured interviews with open and closed questions about PNCG and the interest to participate in tourism activity. As a partial result, it appears that these residents understand the importance to conserve the area, recognizing the negatives aspects implicate the current tourism infrastructure, the natural attractive presents at this National Park and set forth interest to support the Ecotourism segment as a secondary source of employment and income.